A study of quality assessment in SARS-CoV-2 pathogen nucleic acid amplification tests performance; from the results of external quality assessment survey of clinical laboratories in the Tokyo Metropolitan Government external quality assessment program in 2020. Issue 2 (February 2022) - Ishii, Yoshikazu; Aoki, Kotaro; Oda, Mayuko; Ichikawa, Megumi; Moriuchi, Rie; Konishi, Hiroyuki; Nagashima, Mami; Sadamasu, Kenji; Sugishita, Yoshiyuki
Abstract: Introduction: The Tokyo Metropolitan Government (TMG) conducted an external quality assessment (EQA) survey of pathogen nucleic acid amplification tests (NAATs) as a TMG EQA program for SARS-CoV-2 for clinical laboratories in Tokyo. Methods: We diluted and prepared a standard product manufactured by Company A to about 2, 500 copies/mL to make a positive control and distribute it with a negative control. The participants reported the use of the NAATs methods for SARS-CoV-2, the name of the real-time RT-PCR kit, the name of the detection device, the target gene(s), nucleic acid extraction kit, Threshold Cycle value in the case of RT-PCR and the Threshold time value and Differential calculation value in the case of Loop-Mediated Isothermal Amplification (LAMP) method. Results: As a result, 17 laboratories using fully automated equipment and 34 laboratories using the RT-PCR method reported generally appropriate results in this EQA survey. On the other hand, among the laboratories that adopted the LAMP method, there were a plurality of laboratories that judged positive samples to be negative. Conclusion: The false negative result is considered to be due to the fact that the amount of virus genome contained in the quality control reagent used this time was below the detection limit of the LAMP method combined with the rapid extraction reagent for influenza virus. On the other hand, false positive results are considered to be due to the non-specific reaction of the NAATs. The EQA program must be continued for the proper implementation of the pathogen NAATs.